The newest vital sign: a new tool for assessing health literacy in the UK. (18th April 2012) - Khazaezadeh, N; Rowland, G; Oteng-Ntim, E; Barr, S; Weiss, B
Abstract : Background: Health Literacy (HL) is the degree to which individuals can understand and act on basic health information and services to make appropriate decisions. Current UK HL measures have drawbacks in length and acceptability. The US-developed Newest Vital Sign (NVS) uses a nutrition label to assess health-related literacy and numeracy skills in 3 minutes. This study aims to modify and validate a UK version of the NVS. Methods: 3 stages Modify NVS for the UK nutrition labeling using Delphi -expert consensus study. Cognitive testing: 80 participants over 5 test rounds. Validation: against the Test of Functional Health Literacy in Adults (TOFHLA). 337 subjects aged 18 – 75. Findings: The NVS UK was correlated with TOFLAH. Scoring <2 predicted low health literacy: specificity 82%, sensitivity 70%. Scoring >4 predicted adequate health literacy: sensitivity 100% specificity 40%. Discussion: The NVS UK is a valid measure of HL. Its acceptability makes it an ideal tool for HL research.